PENDAFTARAN PERALIHAN HAK ATAS TANAH KARENA PEWARISAN - Habibah Habibah (JOURNAL OF ADMINISTRATIVE AND SOCIAL SCIENCE, 2022)
This study aims to determine the implementation of PP 24/1997 in the process of registering the transfer of land rights due to inheritance based on the statement of heirs, and to find out the process of registering the transfer of rights due to inheritance at the Makassar City Land Office not using the Deed of Sharing Joint Rights as stipulated in PP 24 /1997, but using a statement letter based on heirs. The sampling technique used in this research is purposive sampling, namely the purposeful sampling, which is carried out by taking subjects based on a specific purpose, citing limited time, effort and cost, so it cannot be obtained. taking samples that are large in number and far apart.1 Especially PPAT, the main criterion in determining the sample is PPAT who has been in contact with the Makassar City Land Office in relation to land registration. The results showed that the registration of the transfer of land rights due to inheritance applied by the Makassar City Land Office could be carried out only by making a statement of heirs on the basis of a statement of heirs whose contents designate one of the heirs as the right holder, the registration of the transfer of rights can be directly carried out. without any legal action before the authorized official, namely PPAT, by making a deed of sharing rights together. The process of registering the transfer of rights due to inheritance at the Makassar City Land Office does not use the Deed of Sharing Joint Rights due to strong customary influence so that there are still many community members who transfer land rights under their hands. Keywords: transfer of rights, inheritance, heirs, PPAT